1978
DOI: 10.1073/pnas.75.10.4657
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium nuclear magnetic resonance investigation of the effects of proteins and polypeptides on hydrocarbon chain order in model membrane systems

Abstract: Deuterium Fourier-transform nuclear magnetic resonance spectra have been obtained of 1-myristoyl 2-(14,14,14-trideutero)myristoyl phosphatidylcholine bilayers at 34.1 MHz by using the quadrupole echo pulse technique. Thereby, we have investigated the effects upon the deuterated dimyristoyl phosphatidylcholine bilayers of the following proteins and polypeptides: gramicidin A, bacteriophage f1 coat protein, beef brain myelin proteolipid apoprotein, cytochrome b 5 , and cytochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
69
1

Year Published

1979
1979
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 27 publications
25
69
1
Order By: Relevance
“…In addition since TIP is also shorter in the mixed systems, the relative intensity of the low frequency motion undergone by the acyl chains has increased. This supports the observations in [2] and shows that on the NlvlR timescale employed here (-IO-' s) the effect of lipid-protein or lipidcholesterol interactions is the production of an increase in the low frequency dynamic disorder. Examination of the order resonant peaks shows that apart from minor relative changes in the TC_H and TIP of the headgroup and terminal methyl peaks, the reduction is a general property of the mixed systems.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In addition since TIP is also shorter in the mixed systems, the relative intensity of the low frequency motion undergone by the acyl chains has increased. This supports the observations in [2] and shows that on the NlvlR timescale employed here (-IO-' s) the effect of lipid-protein or lipidcholesterol interactions is the production of an increase in the low frequency dynamic disorder. Examination of the order resonant peaks shows that apart from minor relative changes in the TC_H and TIP of the headgroup and terminal methyl peaks, the reduction is a general property of the mixed systems.…”
Section: Resultssupporting
confidence: 79%
“…Recent deuterium NMR studies of a series of lipid-protein dispersions have shown, however, that the quadrupolar splittings, derived from lipids with deuterated methylene groups, are freq uently reduced compared to those obtained from the same labels in pure lipid bilayers [ 2,7]. These observations have been interpreted as indicating an increase in the amplitude of the low frequency (-10' Hz) motion undergone by the lipid acyl chains in the presence of the protein [2]. It is argued that the frequency of this additional lipid motion is insufficiently rapid to cause a reduction in the hyperfme field splittings seen in the ESR spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Further, evidence exists for rapid exchange between annular lipid and bulk lipid [21], an observation inconsistent with the presence of bound lipid vital to function. This latter observation is at variance with evidence presented for relatively immobilized boundary lipid in reconstituted cytochrome oxidase systems [22], but more recent work is fully consistent with rapid exchange between annular and bulk bilayer lipid [23,24]. Thus, while the possibility remains that the local fluidity or lipid composition may affect protein function, the evidence supporting such proposals as a general rationale for the variety of lipids in biomembranes must be regarded as inconclusive.…”
Section: Ia Functional Roles Of Lipids In the Fluid Mosaic Model Of contrasting
confidence: 53%
“…DISCUSSION Connection to Experiments. There is currently a great deal of discussion about whether membrane proteins order or immobilize nearby lipids (1,3,4,13,14). The present theory models either situation, depending on the value chosen for uo.…”
Section: Resultsmentioning
confidence: 99%
“…7 we estimated that T = 0 lies <20 degrees below the transition temperature. The experiments (13) on which this estimate was based have been criticized (14). The …”
Section: Description Of Theorymentioning
confidence: 99%